تحسين أداء هوائي فيفالدي باستخدام الشق على شكل حرف U لكشف الورم الدماغي - عبد الكريم السالم; ريم العجي (Tishreen University, 2019)
Early detection of brain injuries is the most important factor for reducing the number of deaths around the world. However, a fast and effective imaging system that can be carried in the ambulance has to be developed. This is provided by the microwave imaging system compared with other imaging techniques such as CT scans and magnetic resonance imaging (MRI), Since the antenna is the most important element in the microwave imaging system. In this research, VIVALDI antenna was designed to pass the frequency band of [2.33-7.09] GHz with a maximum gain of 6.62dB. The antenna Specifications was improved by creating a U-shaped slot on the upper layer of the antenna to become bandpass [2.213-7.187] GHz with a maximum gain of 7.36 dB and decrease side lobe levels and thus focus the radiation in the main lobe direction.in this research, Simple head model which consists of brain layer whose dielectric properties were compatible with their natural values  was designed by CST package to test the efficiency of antenna in the microwave imaging system that  by comparing average SAR values, magnetic field H, and electric field E between the healthy head and injured one. يعتبر الكشف المبكر عن الإصابات الدماغية العامل الأهم في تقليل عدد الوفيات حول العالم لذلك كان لابد من تطوير نظام تصوير سريع وفعال يمكن حمله في سيارة الاسعاف وهذا ما يوفره نظام التصوير المكروي بالمقارنة مع تقنيات التصوير الأخرى كالتصوير الطبقي المحوري CT والتصوير بالرنين المغناطيسي MRI، وبما أن الهوائي يعتبر العنصر الأكثر أهمية في نظام التصوير المكروي. فقد تم في هذا البحث تصميم هوائي فيفالدي  عريض الحزمة يعمل على تمرير الحزمة الترددية [2.33-7.09]GHz وبربح أعظمي 6.62dB وتم تحسين أداء هذا الهوائي بإحداث شق على شكل حرف U على الطبقة العلوية من الهوائي لتصبح حزمة التمرير [2.213-7.187]GHz وبربح أعظمي 7.36dB مع تقليل مستوى الحزم الجانبية وبالتالي تركيز الإشعاع في الاتجاه الأمامي.و تم في هذا البحث أيضاً تصميم نموذج رأس وهمي بسيط مكون من طبقة الدماغ وبقيم محددات تنسجم مع قيمتها في الحالة الطبيعية حيث اعتمد التصميم على استخدام الحزمة البرمجية التخصصية CST لاختبار فعالية الهوائي في أنظمة التصوير المكروي وذلك من خلال مقارنة قيم نسبة الامتصاص النوعي SAR والحقل المغناطيسي H والحقل الكهربائيE    بين حالة الرأس السليم والرأس المصاب.